2021
DOI: 10.3390/agriculture11010064
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerant near Isogenic Lines (NILs) of Pusa 44 Developed through Marker Assisted Introgression of qDTY2.1 and qDTY3.1 Enhances Yield under Reproductive Stage Drought Stress

Abstract: Reproductive stage drought stress (RSDS) is detrimental for rice, which affects its productivity as well as grain quality. In the present study, we introgressed two major quantitative trait loci (QTLs), namely, qDTY2.1 and qDTY3.1, governing RSDS tolerance in a popular high yielding non-aromatic rice cultivar, Pusa 44, through marker-assisted backcross breeding (MABB). Pusa 44 is highly sensitive to RSDS, which restricts its cultivation across drought-prone environments. Foreground selection was carried out us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Out of the several QTLs reported for reproductive stage drought tolerance in rice, qDTY1.1 [15,16], qDTY2.1 [33], qDTY3.1 [33,49] and qDTY12.1 [50,51], showed consistent grain yield under drought across different genetic backgrounds and has been used in breeding applications. Recently, Dwivedi et al [23] reported successful pyramiding of two QTLs, qDTY2.1 and qDTY3.1 into the megavariety, Pusa 44 significantly enhancing yield under drought. Despite the proven advantage, however, only few success stories in improving rice varieties for drought tolerance using MABB has been reported rice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the several QTLs reported for reproductive stage drought tolerance in rice, qDTY1.1 [15,16], qDTY2.1 [33], qDTY3.1 [33,49] and qDTY12.1 [50,51], showed consistent grain yield under drought across different genetic backgrounds and has been used in breeding applications. Recently, Dwivedi et al [23] reported successful pyramiding of two QTLs, qDTY2.1 and qDTY3.1 into the megavariety, Pusa 44 significantly enhancing yield under drought. Despite the proven advantage, however, only few success stories in improving rice varieties for drought tolerance using MABB has been reported rice.…”
Section: Discussionmentioning
confidence: 99%
“…Marker assisted introgression of major-effect QTLs could be a proficient and rapid approach for breeding rice varieties tolerance to drought stress [17]. Consequent attempts to introgress/pyramid these QTLs by marker assisted selection, primarily into mega-varieties has found significant advancements towards breeding climate-adaptive cultivars [19,20], such as Sabitri (qDTY3.2 and qDTY12.1) [21], IR 64 (qDTY2.2 and qDTY4.1), Vandana (qDTY12.1) [22] and Pusa 44 [23]. In the past twelve years, there has been about sixtysix RSDS tolerant varieties released around the world, which involve several of these QTLs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Pusa 44 has been a prominent choice among the non-Basmati rice varieties for improvement due to the advantages described earlier. Recent developments in the improvement of Pusa 44 by the introgression of QTLs imparting RSDS tolerance such as qDTY2.1 and qDTY3.1 were reported by Dwivedi et al [ 15 ] and Oo et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In India, Pusa 44 is a medium- to long-duration and highly productive mega variety cultivated across the northwestern plain zone, particularly in Punjab and Haryana. Pusa 44 was developed and released by the Indian Council of Agricultural Research (ICAR)-Indian Agricultural Research Institute (IARI), New Delhi solely for the irrigated lowland ecology [ 15 ]. Catering to the livelihood of thousands of rice farmers, Pusa 44 is grown extensively in northwestern India, and is widely popular due to its high yield potential (7.0–8.0 t.ha −1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation